Comparison of two commercial kits for identifying and biotyping Haemophilus parainfluenzae. Issue 1 (January 1991) - Warren, M; Ahmet, Z; Houang, E
Abstract : The Minitek system and the more recently introduced Micro Scan HNID panels for the identification and biotyping of 98 V dependent Haemophilus isolates were compared. Identical results were obtained for 77 isolates. The discrepancy in the results of ornithine and urease was accounted for mainly by the mismatching of the identification by the two kits. When 13 isolates of H parainfluenzae with mismatched biotypes were re-examined, the results from Micro Scan correlated with 92% of those obtained by Christensen's urea broth and 100% by the ornithine test (Lab M); the corresponding figures for Minitek were 61% and 30%, respectively. Micro Scan was easy to handle on the bench and results were ready on the same day. These results suggest that further work is required to assess these two systems for the biotyping of H parainfluenzae.